The Role Of Social Media Marketing And Pricing In Influencing Purchasing Decisions Of Msmes In Padangsidimpuan City - Sari, Adelina Puspita; Ihsan Effendi; Lubis, Adelina (Proceeding of The International Conference on Business and Economics, 2024)
This study aims to analyze the role of Social Media Marketing and pricing in influencing consumer purchasing decisions at Tabona Dessert MSMEs in Padangsidimpuan City. Social Media Marketing has become one of the main marketing strategies for MSMEs, especially in increasing visibility and market reach. On the other hand, pricing is an important factor that can influence consumer perceptions of value and purchasing decisions. This study uses a quantitative method with data collection through a questionnaire survey distributed to consumers of Tabona Dessert MSMEs in Padangsidimpuan City. The data obtained were analyzed using multiple regression techniques to see the effect of Social Media Marketing and pricing on purchasing decisions. The results of the study indicate that Social Media Marketing has a significant influence on purchasing decisions, where effective marketing strategies on social media can increase consumer interest and awareness of MSME products. In addition, pricing has also been shown to have a significant effect, where competitive prices and in accordance with product quality are the main considerations for consumers in making purchasing decisions. In conclusion, the combination of effective Social Media Marketing and appropriate pricing can significantly increase consumer purchasing decisions for Tabona Dessert MSME products in Padangsidimpuan City.